Effects and molecular mechanism of chitosan-coated levodopa nanoliposomes on behavior of dyskinesia rats. Issue 1 (December 2016) - Cao, Xuebing; Hou, Dongzhi; Wang, Lei; Li, Sai; Sun, Shengang; Ping, Qineng; Xu, Yan
Abstract Background Chitosan, the N-deacetylated derivative of chitin, is a cationic polyelectrolyte due to the presence of amino groups, one of the few occurring in nature. The use of chitosan in protein and drug delivery systems is being actively researched and reported in the literature. Results In this study, we used chitosan-coated levodopa liposomes to investigate the behavioral character and the expression of phosphorylated extracellular signal-regulated kinase (ERK1/2), dopamine- and cAMP-regulated phosphoprotein of 32 kDa (DARPP-32) and FosB/ΔFosB in striatum of rat model of levodopa-induced dyskinesia (LID). We found that scores of abnormal involuntary movement (AIM) decreased significantly in liposome group (P < 0.05), compared with levodopa group. Levels of phospho-ERK1/2, phospho-Thr34 DARPP-32 and FosB/ΔFosB in striatum decreased significantly in liposome group lesion side compared with levodopa group (P < 0.05). However, both of two groups above have significantly differences compared with the control group (P < 0.05). Conclusion Chitosan-coated levodopa liposomes may be useful in reducing dyskinesias inducing for Parkinson disease. The mechanism might be involved the pathway of signaling molecular phospho-ERK1/2, phospho-Thr34 DARPP-32 and ΔFosB in striatum.